Disagreement about Future Inflation : Understanding the Benefits of Inflation Targeting and Transparency - Brito, Steve; Carriere-Swallow, Yan.; Gruss, Bertrand (Washington, D.C. : International Monetary Fund, 2018)
We estimate the determinants of disagreement about future inflation in a large and diverse sample of countries, focusing on the role of monetary policy frameworks. We offer novel insights that allow us to reconcile mixed findings in the literature on the benefits of inflation targeting regimes and central bank transparency. The reduction in disagreement that follows the adoption of inflation targeting is entirely due to increased central bank transparency. Since the benefits of increased transparency are non-linear, the gains from inflation targeting adoption have accrued mainly to countries that started from a low level of transparency. These have tended to be developing countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Central Bank Transparency; Inflation Forecasts; Inflation Targeting; IT Adoption; WP; United States